Comprehensive Transcriptome Sequencing Analysis of Hirudinaria manillensis in Different Growth Periods - Shan, Huiquan; Ren, Ke; Liu, Jiasheng; Rehman, Saif ur; Yan, Xiuying; Ma, Xiaocong; Zheng, Yalin; Feng, Tong; Wang, Xiaobo; Li, Zhipeng; Zhou, Weiguan; Chuang, Chen; et al. (Frontiers in Physiology, 2022)
Medical leeches are widely used in biochemical and clinical medical studies-helping to restore blood circulation to grafted or severely injured tissue et. al. Mostly, adult leeches were used, but the gene expression profiles of different growth periods of leeches were few reported. In the current study, the gene expression patterns of Hirudinaria manillensis in different growth periods by transcriptome analysis were compared. We constructed 24 cDNA libraries using the samples from larval stage, young stage and adult stage Hirudinaria manillensis, a total of 54,639,118 sequences were generated, 18106 mRNAs transcripts and 958 new mRNAs transcriptions, 491 lncRNAs were assembled. The further GO and KEGG enrichment analysis results showed that the differentially up-regulated genes in the larval to adult periods were enriched in pathways such as cilium, myofibril, contractile fiber, Cytoskeleton proteins, Dilated cardiomyopathy, Adrenergic signaling in cardiomyocytes, and so on. We also found a significant increase in the expression of the Hirudin-HM (HIRM2) genes during the adult stage. A comprehensive transcriptome profiles from different growth periods of Hirudinaria manillensis were progressed and a large number of DEGs and DElncRNAs were identified which tentatively found that as Hirudinaria manillensis grew, muscle-related genes expression increased, the lipid metabolism decreased, the need for stimulation and nutrition decreased, and the high expression of HIRM2 may be related to the high expression of PDI family genes in adulthood provide an important clue that why adult leeches (not young leeches ) were widely used in clinical therapeutics and Chinese medicine.